Philosophy of science - Kononovich, Lila; Garcia, Pablo; Films for the Humanities & Sciences (New jersey : Films for the Humanities & Sciences, 2004)
This program seeks to answer questions such as these through the insights of Princeton University's Daniel Garber; Hilary Putnam, of Harvard University; and Barry Loewer, of Rutgers University. Ranging from the Physics of Aristotle to the competing physics paradigms of Einstein and Bohr, the program illustrates the progression of scientific thought from ancient times, through the Renaissance, to the 21st century
Title from title screen
Executive producers, Chris Scherer, Camila O'Donnell
Narrator: Liz Chang, Juan Antonio Middleton
DVD format
Keywords: Philosophy; Philosophy -- History; Philosophy and science; Science -- Philosophy